Emerging Contaminants from Industrial and Municipal Waste - Barceló, Damià. (Springer, 2017)
This book focuses on innovative treatment technologies for the elimination of emerging contaminants in wastewater and drinking water treatment processes. The book also discusses sources and occurrence of emerging contaminants in municipal and industrial waste, giving an overview of state-of-the-art analytical methods for their identification. Further important aspects covered include the acute and chronic effects and overall impact of emerging contaminants on the environment.